(3efThQ Edi Bd YHO Gddgs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje cJGHfG Edjce CjgG GdENhGf GdCWgGQ hGdSaQI GdCHQGQ GdehMOhf GdCRgGQ CWGd Gdg ai Xd QMeJg HbGce s
(3BNQgG (B:s
(3fNU LeGYJce GdUZjQ hGdcHjQ hGdHYjO hGdbQjH HCJe GdJMjI hGdSdGe hdh Cecf dWdHfG GdLhGH hGdMeO dehdGfG hMOg hGdTcQ dhdi GdReGf YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B88s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3abg GdePGgH GdCNQis